2020
DOI: 10.3389/fbioe.2020.597721
|View full text |Cite
|
Sign up to set email alerts
|

Endomembranes: Unsung Heroes of Mechanobiology?

Abstract: Mechanical stimuli have profound effects on the cellular architecture and functions. Over the past two decades, considerable progress has been made in unraveling the molecular machineries that confer cells the ability to sense and transduce mechanical input into biochemical signals. This has resulted in the identification of several forcesensing proteins or mechanically activated ion channels distributed throughout most cell types, whereby the plasma membrane, cytoskeleton, and the nucleus have garnered much a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…However, how external forces are transmitted from the plasma membrane to mitochondria is still largely unexplored. As for other endomembranes (Phuyal & Baschieri, 2020) and for the nucleus, the cytoskeleton is probably a major actor. Several studies have shown that external mechanical stimulation of either intracellular or isolated mitochondria increase fission or fusion events (Phuyal et al, 2023).…”
Section: External Forces Reshape the Mitochondrial Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, how external forces are transmitted from the plasma membrane to mitochondria is still largely unexplored. As for other endomembranes (Phuyal & Baschieri, 2020) and for the nucleus, the cytoskeleton is probably a major actor. Several studies have shown that external mechanical stimulation of either intracellular or isolated mitochondria increase fission or fusion events (Phuyal et al, 2023).…”
Section: External Forces Reshape the Mitochondrial Networkmentioning
confidence: 99%
“…Cells sense and process signals from their external environment to coordinate structural and functional processes such as growth, proliferation, homeostasis and compressive, tensile or shear stresses are transmitted into the cell through the coordinated activity of mechanosensors along mechanosignaling pathways. Previous studies have investigated and reviewed the role of the plasma membrane, mechano-activated ion channels, focal adhesion proteins, cytoskeletal filaments (actin, microtubule and intermediate filaments) and the nucleus in sensing and transducing mechanical stresses (Ingber, 2006;Orr et al, 2006;Jaalouk & Lammerding, 2009;Schwartz, 2010;Isermann & Lammerding, 2013;Douguet & Honoré, 2019;Kechagia et al, 2019;Uray & Uray, 2021), but the molecular mechanisms of mechanotransduction are still incompletely understood, in particular when intracellular compartments such as the endomembrane system are involved (Phuyal & Baschieri, 2020;Phuyal et al, 2023). With the spurring growth of intracellular rheology, the mechanical properties of the cytoplasm, intracellular organelles and the cytoskeleton emerge as key players in both mechanosensing and mechanotransduction (Mathieu & Manneville, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The complex structure of the ER is also highly dynamic and changes according to the cell’s requirements. What regulates the changes is still not fully understood, but the ER network is constantly rearranging and redistributing, aided by multiple factors [ 33 , 34 , 35 ] and has even been found to be sensitive to mechanical stimuli [ 36 ].…”
Section: General Er Morphology In Cellsmentioning
confidence: 99%
“…It is now well established that such mechanical cues trigger signaling pathways that mediate changes in cell differentiation, proliferation, growth, and survival (Engler et al , 2006 ; Roca‐Cusachs et al , 2013 ; Gudipaty et al , 2017 ; Janmey et al , 2020 ). Most research in the area of mechanobiology has focused on the plasma membrane, the nucleus, or the cytoskeleton as receivers and mediators of mechanical signaling (Phuyal & Baschieri, 2020 ). However, it is currently poorly understood whether and how mechanical stress has any effect on early secretory pathway compartments such as ERES.…”
Section: Introductionmentioning
confidence: 99%